Vaccination with dendritic cells pulsed with hepatitis C pseudo particles induces specific immune responses in mice - Weigand, Kilian (Baishideng Publishing Group Co., Limited, 2012)
AIM: To explore dendritic cells (DCs) multiple functions in immune modulation. METHODS: We used bone-marrow derived dendritic cells from BALB/c mice pulsed with pseudo particles from the hepatitis C virus to vaccinate naive BALB/c mice. Hepatitis C virus (HCV) pseudo particles consist of the genotype 1b derived envelope proteins E1 and E2, covering a non-HCV core structure. Thus, not a single epitope, but the whole “viral surface” induces immunogenicity. For vaccination, mature and activated DC were injected subcutaneously twice. RESULTS: Humoral and cellular immune responses measured by enzyme-linked immunosorbent assay and interferon-gamma enzyme-linked immunosorbent spot test showed antibody production as well as T-cells directed against HCV. Furthermore, T-cell responses confirmed two highly immunogenic regions in E1 and E2 outside the hypervariable region 1. CONCLUSION: Our results indicate dendritic cells as a promising vaccination model for HCV infection that should be evaluated further.